2004
DOI: 10.1159/000077977
|View full text |Cite
|
Sign up to set email alerts
|

Second Autologous Transplantation for Multiple Myeloma Patients Relapsing after the First Autograft – a Pilot Study for the Evaluation of Experimental Maintenance Therapies. Report of the Prospective Non-Randomized Pilot Study of the Czech Myeloma Group

Abstract: Background: High-dose chemotherapy followed by autologous stem cell transplantation (AT) is accepted as first-line therapy for patients with multiple myeloma (MM), with very good tolerance and low mortality (2–3%). Study Design: We tested repeated transplantation with different experimental maintenance therapies in patients with MM relapsing/progressing after first AT. Results were compared using intra-individual analyses, therefore inter-individual differences are excluded (T2 model). Patients and Methods: Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Regimens based on conventional chemotherapy have included high-dose dexamethasone (18,19) (27), and then, further developed by Barlogie and colleagues, who showed that myeloablative doses of melphalan with appropriate hematopoietic stem cell support could overcome resistance to conventional-dose chemotherapy in this group of patients (28,29). Available data on second autologous transplants for relapsed patients suggest that these procedures are relatively well tolerated, with a 100-day mortality of <10% (30)(31)(32)(33). Recent studies using second salvage transplants include a sizeable proportion of patients who have received novel agents in the induction setting.…”
Section: Relapse Definitionmentioning
confidence: 99%
“…Regimens based on conventional chemotherapy have included high-dose dexamethasone (18,19) (27), and then, further developed by Barlogie and colleagues, who showed that myeloablative doses of melphalan with appropriate hematopoietic stem cell support could overcome resistance to conventional-dose chemotherapy in this group of patients (28,29). Available data on second autologous transplants for relapsed patients suggest that these procedures are relatively well tolerated, with a 100-day mortality of <10% (30)(31)(32)(33). Recent studies using second salvage transplants include a sizeable proportion of patients who have received novel agents in the induction setting.…”
Section: Relapse Definitionmentioning
confidence: 99%
“…Even in relapsed disease, remissions can be obtained in the majority of patients 4,5 although these tend to be shorter than first treatment responses. 6,7 Extramedullary myeloma is not frequent but is always associated with a significantly shorter overall survival, even in the era of novel agents. 3,[8][9][10][11][12] Extramedullary myeloma (EM) is a type of MM defined by the presence of extraskeletal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…GVHD responded promptly, and prednisolone was discontinued by salvage ASCT was ranged from 0% to 14.3%. 5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20]22 So far, the outcomes of salvage ASCT in Japan have not been published. Accordingly, we aimed to conduct a retrospective study to clarify the outcome of ASCT and its significance on overall survival(OS)in patients with relapsed MM.…”
Section: Case Reportmentioning
confidence: 99%
“…In Western countries, secondary ASCT with HD-MEL as a salvage therapy(salvage ASCT)for patients who have a relapse after up-font ASCT has been used in clinical practice. The median PFS after salvage ASCT ranged from 5 to 22 months, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the overall response rate ranged from 53.3 to 97.4%. 5,[7][8][9][10][11][12][13][14][15][17][18][19][20][21][22] The median treatment-related mortality rate associated with…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation